Reevaluation of the intraspecific variability in Darevskia parvula (Lantz & Cyren, 1913): an integrated approach using morphology, osteology and genetics (Squamata: Lacertidae) - Arribas, Oscar; Ilgaz, Çeti̇n; Kumlutaş, Yusuf (Zootaxa, 2018)
The intraspecific variability of Darevskia parvula (which has two classical subspecies easily identifiable by external characteristics, D. p. parvula and D. p. adjarica), was studied using various approaches including morphology (scalation and biometry), multivariate analyses (PCA, CDA, ANOSIM, UPGMA and MST), osteology, and molecular techniques. High mitochondrial distance, differences at the nuclear level and morphological distinctiveness warrant the specific status of both taxa, Darevskia parvula (Lantz & Cyrén, 1913) and Darevskia adjarica (Darevsky & Eiselt, 1980) stat. nov. A lectotype for D. parvula, originally described with syntypes of both species -D. parvula and D. adjarica- is designated. The uncorrected genetic distance between D. parvula and D. adjarica in the cytochrome b mitochondrial gene is 14.4% ± 1.9%. Intraspecific variability within D. parvula is very small (1.5% ± 0.5%), and was not detected in our samples of D. adjarica. The two species further differ by two mutations in the nuclear melano-cortin 1 receptor (mc1r) gene. Interestingly, past introgression of D. parvula mitochondrial haplotypes (5% ± 1% different to those currently known) into some D. adjarica has been detected in one locality; all the studied specimens of D. adjarica with mtDNA of D. parvula are unmistakably D. adjarica at the morphological and nuclear levels.Morphologically, there is almost no overlap between D. parvula and D. adjarica. These results are corroborated by CDA, MST and UPGMA trees. Specimens of the inland high mountain population of Ardahan (clearly D. adjarica in CDA, MST and UPGMA trees) occupy a somewhat intermediate position between both taxa in the PCA (when specimens and not populations as a whole are considered), but this morphological closeness may be attributed to the influence of climatic factors (continental conditions) on scalation of the specimens. Males appear to be more differentiated than females. Overlap among samples within each species is very marked; none can be separated clearly from its conspecifics. This is even more marked in D. parvula, which has a fairly small area compared to D. adjarica.Darevskia parvula and D. adjarica samples appear to be homogeneously clustered within species and well separated between the two species in the UPGMA trees. In males and females all the D. parvula samples are very similar and moderately differentiated. In males of D. adjarica, the most differentiated seems to be adjBorçka, the others all being clustered together, with adjÇaykara showing slightly more differentiation from the rest (adjOrtacalar, adjArdahan, adjIkizdere and adjÇermik).Darevskia adjarica females are also similarly distributed into two subgroups, one including Borçka, Çermik and Ardahan and the other including Ortacalar, Ikizdere and Çaykara. In both sexes, the inland Ardahan sample clearly belongs to D. adjarica.From the most connected MST samples, speculations can be made about areas of origin and expansion of the different taxa. Ortacalar (D. adjarica) and Hatila (D. parvula) are the most connected (morphologically more “central” in both taxa); in fact, both populations are relatively close, living on the northern (Black Sea) and southern (Anatolian) facing slopes, respectively of the Doğu Karadeniz Mountains (Kaçkar Mountains). This highlights these mountains, which rise from sea level up to nearly 4000 m asl. and have wide buffering possibilities against climate changes, as a zone of refuge and posterior dispersion of this species, and even of the original splitting into two taxa adapted to these different conditions, D. adjarica on the coast and D. parvula on the continental slope.Osteologically D. parvula and D. adjarica are very similar, although Georgian specimens from an isolated population (Atskuri) have closed clavicles not found in Turkish D. adjarica. Also, inland Ardahan D. adjarica have an extra vertebra in both males and females, compared to the other studied specimens from both species.The present study indicates that the situation in Turkey is that D. parvula is well differentiated and lives around the Çoruh River Valley, contoured by D. adjarica populations on the coastal-facing slopes of the Doğu Karadeniz Mountains on one side, and the Yalnızçam Mountains on the other side, where D. adjarica enters from Georgia as the opposite extreme of a geographic distribution. The attribution of more inland ranges to D. parvula or D. adjarica, as well as the detailed genetic structure of both taxa may be confirmed with more specific studies.